2008
DOI: 10.1007/s00296-008-0590-z
|View full text |Cite
|
Sign up to set email alerts
|

A case of AA amyloidosis associated with rheumatoid arthritis effectively treated with Infliximab

Abstract: We report the case of a 55-year-old Japanese woman with reactive AA amyloidosis associated with rheumatoid arthritis, in which inflammatory disease was completely suppressed with infliximab. Nephrotic syndrome was observed and renal biopsy specimens revealed amyloidosis deposits. Treatment with infliximab normalized the serum amyloid A (SAA) protein level, and subsequently nephritic syndrome disappeared and her creatinine clearance improved. Serial gastrointestinal biopsy specimens showed marked lasting regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…(21) GI amyloidosis in RA, including upper GI lesion, has recently been reported to be improved by treatment with such biologics as infliximab and tocilizumab. (22,23) Since the prevalence of GI amyloidosis was reported around 10% by histological evaluation of stomach and duodenum biopsy, (24,25) patients with upper GI amyloidosis could have been included in our study. Unfortunately, however, we did not perform endoscopy and biopsy in this study, and it is unclear whether such histological disorders as amyloidosis were included and whether they associated with GERD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…(21) GI amyloidosis in RA, including upper GI lesion, has recently been reported to be improved by treatment with such biologics as infliximab and tocilizumab. (22,23) Since the prevalence of GI amyloidosis was reported around 10% by histological evaluation of stomach and duodenum biopsy, (24,25) patients with upper GI amyloidosis could have been included in our study. Unfortunately, however, we did not perform endoscopy and biopsy in this study, and it is unclear whether such histological disorders as amyloidosis were included and whether they associated with GERD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study and several case reports have already indicated that such agents are effective against AA amyloidosis [25][26][27][28][29][30] . A retrospective study and several case reports have already indicated that such agents are effective against AA amyloidosis [25][26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the therapeutic potential of anti-tumor necrosis factor-α (anti-TNF) or anti-interleukin 6 (anti-IL-6) agents for AA amyloidosis secondary to inflammatory arthritides, including RA [25][26][27][28][29][30] , but the significance of any improvement in tissue levels has not been fully evaluated.…”
mentioning
confidence: 99%
“…Her diarrhea rapidly subsided, but edema was persistent and her serum albumin level did not recover. Next, we empirically tried adalimumab administration, because TNF-blocking agents are the second best choice as they can work fast to control active RA if it is intractable to glucocorticoid, and there were reports that etanercept and infliximab can reduce serum amyloid A levels in RA patients with AA amyloidosis [6,22]. However, there was no immediate response to the TNF-blocking agent.…”
Section: Discussionmentioning
confidence: 99%